Effectiveness of Digital Therapeutics (DTx) on mental health for teenagers: an Islamic design perspective - Zannat, Nahreen; Mahmud, Murni (myHCI-UX, 2022)
Stable mental health and well-being are key concerns for human beings seeking contentment in all parts of life. During the COVID-19 pandemic, the rising pressure and stress have resulted in financial struggles and increased anxiety, panic episodes and suicide among many, including teenagers. Due to the prolonged lockdown and closure of institutions, teenagers face isolation and encounter more troubles than before. Consequently, the use and reliance on the Internet, especially mobile applications and other digital solutions, are soaring and becoming more intrusive in every sector. In the medical field, Digital Therapeutics (DTx) has appeared as one of the health solutions based on evidence from therapeutic interventions driven by software to prevent diseases and illnesses. Some DTxs are specifically designed and developed to cater to mental health conditions. However, previous literature has shown limited understanding and impact of Islamic design and content for DTx features. Therefore, this paper aims to explore the significance of DTx in teenagers’ lives and identify the design and content features within an established understanding from an Islamic perspective. In this paper, the authors intend to address the effectiveness of DTx, which will lessen the challenges of mental health issues and ensure the well-being of teenagers.